TAFSSA District Agrifood Systems Assessment in Nepal 2023: Adolescent - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
TAFSSA (Transforming Agrifood Systems in South Asia) is a CGIAR Regional Integrated Initiative dedicated to supporting actions that enhance equitable access to sustainable, healthy diets, improve farmers' livelihoods and resilience, and conserve land, air, and water resources in South Asia. The TAFSSA district agrifood systems assessment aims to establish a reliable, accessible, and integrated evidence base linking farm production, market access, dietary patterns, climate risk responses, and natural resource management, with a focus on gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. The assessment is designed as a multi-year initiative at the district level. Data collection took place in March-April 2023 in the Surkhet and Banke districts in Nepal. For each household, three respondents were interviewed: a female adult (aged 20+ years) primarily responsible for managing the household, a male adult (aged 20+ years) primarily responsible for agricultural activities, and an adolescent (aged 10-19 years). Additionally, the assessment involved a community questionnaire, where a key informant from each district village was interviewed. Interviews with adolescent household respondents utilized pretested, structured questionnaires. Information was gathered on food intake in the past 24 hours, school attendance, and aspirations.